Perception of Shoppers on Visual Merchandising in a Philippine City - Freshtille Mae Cuello (Philippine Association of Institutions for Research, Inc., 2020)
Rivalry in mall operations has painted a new shopping culture that is aimed at providing shoppers the necessary convenience and pampering they deserve. The use of visual merchandising is a means of orchestrating a distinct, worthwhile, and pleasurable shopping experience. It is a soundless and effective marketing tool that communicates to the customers in a matter of seconds and instantly triggers their impulse whether to buy or not. This study describes customers' views toward important factors of visual merchandising utilized by retail or department stores or malls to influence their purchasing behavior. The descriptive research method was employed in the study to explain the characteristics of mall-goers. Ninety percent of shoppers usually notice visual presentations of malls, and yet the majority of the shoppers made no buying decision based on impulse or visual effects alone. A simple store environment is enough for them. The top three factors of VM that influence their preference on retail or department stores or malls to visit - well-planned store arrangement and layout, courteous salesperson, and product assortment and broad aisles and more spaces. Customers usually tend to engage in impulse shopping behavior when retail or department store or mall deals and other enticing offers are material, especially those that are price related.